PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BKKBN PUSAT - Ahmad Faisal; Erwansyah Sjarief; Muliani Panjaitan (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2023)
The purpose of this study was to determine the influence of Organizational Culture, Job Satisfaction, and Work Motivation on Employee Performance at the Central National Population and Family Planning Board (BKKBN). This research was conducted using a quantitative research approach, using survey methods, including survey activities, consolidation, instrument trials through validity and reliability tests as well as collection and processing of research data. The sample in this study was 133 employees at the Deputy for Latbang Sector of the Central BKKBN. The data collection technique in this study used a random sampling technique, meaning random sampling. Measurement in this study was carried out by giving the value of each question item from all variables. The size of the value given in each question uses a